2020
DOI: 10.1140/epjc/s10052-020-7617-3
|View full text |Cite
|
Sign up to set email alerts
|

openQ*D code: a versatile tool for QCD+QED simulations

Abstract: We present the open-source package openQ*D-1.0 [1], which has been primarily, but not uniquely, designed to perform lattice simulations of QCD+QED and QCD, with and without C * boundary conditions, and O(a) improved Wilson fermions. The use of C * boundary conditions in the spatial direction allows for a local and gauge-invariant formulation of QCD+QED in finite volume, and provides a theoretically clean setup to calculate isospin-breaking and radiative corrections to hadronic observables from first principles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
(95 reference statements)
0
24
0
Order By: Relevance
“…Figure 1 shows all the simulated data types using a reduction data type of binary64, meaning that all reduction operations where conducted in binary64 . The following hierarchy is expected (smaller means convergence in fewer steps): (1) where bfloat16 could be either at position (1) or (2), depending on what is more important; precision or number range.…”
Section: Conjugate Gradientmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 shows all the simulated data types using a reduction data type of binary64, meaning that all reduction operations where conducted in binary64 . The following hierarchy is expected (smaller means convergence in fewer steps): (1) where bfloat16 could be either at position (1) or (2), depending on what is more important; precision or number range.…”
Section: Conjugate Gradientmentioning
confidence: 99%
“…See line 429ff in modules/linsolv/cgne.c in [2] To produce the plots, the Dirac operator Dop_dble() was extracted in binary64 format from the original code running a simulation of a 4 4 lattice, Schrödinger Functional (SF) boundary conditions (type 1), no C ★ boundary conditions (cstar ) and 1 rank. The first 2000 trajectories were considered thermalisation.…”
Section: Conjugate Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…The set up of [6,7,8] has proved to have had a wide use in a variety of lattice problems involving quark bilinear operators. For instance, a non-exhaustive representation set of recent studies can be found in [11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%